The ability of community based natural resource management to contribute to development as freedom and the role of access. (August 2019) - Addison, Jane; Stoeckl, Natalie; Larson, Silva; Jarvis, Diane; Bidan Aboriginal Corporation,; Bunuba Dawangarri Aboriginal Corporation RNTBC,; Ewamian Aboriginal Corporation RNTBC,; Gooniyandi Aboriginal Corporation RNTBC,; Yanunijarra Ngurrara Aboriginal Corporation RNTBC,; Esparon, Michelle
Highlights: Issues of access and different understandings of development limit the generation of social benefits in community NRM. Australian Indigenous communities see development as Sen's 'freedom' The State sees development as a pre-defined set of functionings. Despite these differences, 'freedom' can be progressed through the use of NRM programmes to overcome problems of access. Less prescriptive conditions are likely to promote freedom and stronger community engagement with programs. Abstract: Ribot's access constraints mediate the generation of development benefits from community based natural resource management and co-management systems and programs. Context-specific access constraints also interact with diverse understandings of what constitutes development to create benefits that are non-linear through time, multi or uni-level, prone to hysteresis, socially mediated, vary through space and experienced quite differently by different social actors. In hybridized State-community governance arrangements, this complexity results in ongoing tensions and entanglements as different social actors seek to leverage available opportunities to overcome or circumvent short or longer-term access constraints in pursuit of their understanding of development. In turn, this complexity makes it difficult to understand the full suite of potential development benefits generated by community based natural resource management or co-management structures. Here, we explore potentially competing conceptualisations of development, and the contribution of community based natural resource management to these understandings of development. Using Australia's Indigenous Land and Sea Management Programs to inform this exploration, we show that development is primarily conceptualised as 'control, leadership, empowerment and independence, ' in line with Sen's development as freedom, by the Indigenous groups involved in these programs. State actors understand development in ways that more closely align with Sen's functionings, or a capability list – for example, the relative uptake of jobs and training. Despite this potential mismatch, some Indigenous groups have been able to leverage opportunities available to them, including those provided by the programs, to overcome access constraints to their understandings of 'freedom'. We conclude by offering suggestions as to how community based natural resource management programs could be improved.